How Do Fear-Avoidance and Catastrophizing Pain Beliefs Affect Functional Status and Disease Activity in Axial Spondyloarthritis? - Carlos Fernández-Morales; María de los Ángeles Cardero-Durán; Manuel Albornoz-Cabello; Luis Espejo-Antúnez (Medicina)
Background and Objectives: The objective of our study was to describe the biopsychosocial profile of individuals diagnosed with axial spondyloarthritis (AxSpA) and to analyze how their clinical characteristics interact with disease activity. Materials and Methods: An observational study was conducted, involving 28 participants diagnosed with AxSpA. We evaluated clinical outcomes (perceived pain, range of motion [RoM], pressure pain threshold [PPT], and proprioceptive acuity), psychosocial outcomes (the Pain Catastrophizing Scale [PCS], Tampa Scale of Kinesiophobia [TSK-11], and the Fear-Avoidance Beliefs Questionnaire [FABQ]), and AxSpA-specific indices (the Bath Ankylosing Spondylitis Metrology Index [BASMI], Bath Ankylosing Spondylitis Functional Index [BASFI], and Bath Ankylosing Spondylitis Disease Activity Index [BASDAI]). Data were analyzed using Spearman’s correlation coefficients and simple and multiple linear regression models. Results: Cervical and lumbar RoM values were reduced compared to established normative values for the general population. Significant associations were found between perceived pain, pain catastrophizing, and FABQ scores with both BASDAI and BASFI (p < 0.05). The interaction between perceived pain and pain catastrophizing (p < 0.001) accounted for 45.7% of the variance in BASDAI, while the interaction between perceived pain and FABQ (p < 0.001) explained 52.1% of the variance in BASDAI. Conclusions: The biopsychosocial profile of patients with AxSpA is characterized by moderate-intensity perceived pain and reduced cervical and lumbar mobility. The observed associations between BASDAI, pain catastrophizing, and fear-avoidance beliefs underscore the influence of psychosocial factors on disease progression.